Transplantation of committed pre-adipocytes from brown adipose tissue improves whole-body glucose homeostasis - Revati S. Dewal; Felix T. Yang; Lisa A. Baer; Pablo Vidal; Diego Hernandez-Saavedra; Nickolai P. Seculov; Adhideb Ghosh; Falko Noé; Olivia Togliatti; Lexis Hughes; Megan K. DeBari; Michael D. West; et al. (iScience, 2024)
Summary: Obesity and its co-morbidities including type 2 diabetes are increasing at epidemic rates in the U.S. and worldwide. Brown adipose tissue (BAT) is a potential therapeutic to combat obesity and type 2 diabetes. Increasing BAT mass by transplantation improves metabolic health in rodents, but its clinical translation remains a challenge. Here, we investigated if transplantation of 2–4 million differentiated brown pre-adipocytes from mouse BAT stromal fraction (SVF) or human pluripotent stem cells (hPSCs) could improve metabolic health. Transplantation of differentiated brown pre-adipocytes, termed “committed pre-adipocytes” from BAT SVF from mice or derived from hPSCs improves glucose homeostasis and insulin sensitivity in recipient mice under conditions of diet-induced obesity, and this improvement is mediated through the collaborative actions of the liver transcriptome, tissue AKT signaling, and FGF21. These data demonstrate that transplantation of a small number of brown adipocytes has significant long-term translational and therapeutic potential to improve glucose metabolism.